2021
DOI: 10.21203/rs.3.rs-1008988/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ustekinumab Trough Levels Predicting Laboratory and Endoscopic Remission in Patients with Crohn’s Disease

Abstract: Backgrounds: Optimal concentration of ustekinumab (UST) predicting endoscopic remission has not been fully investigated in Crohn’s disease (CD). We aimed to identify the optimal UST trough levels predicting clinical, laboratory and endoscopic remission in CD patients. Methods: Twenty-eight patients with CD were enrolled and investigated (27 patients by enteroscopy and 1 by colonoscopy). The endoscopic activity was assessed using the modified Rutgeerts scoring system. Serum UST trough levels and anti-UST antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Mucosal inflammation has been suggested to mediate ustekinumab pharmacokinetics as well. [11]. In patients with Crohn's disease who were refractory or intolerant to anti-TNF therapy, Battat et al observed mean ustekinumab trough concentrations of 4.7 and 3.8 μg/mL in patients with and without endoscopic response, respectively, while on maintenance therapy of ustekinumab 90 mg primarily every four weeks (42 of 56 patients) [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mucosal inflammation has been suggested to mediate ustekinumab pharmacokinetics as well. [11]. In patients with Crohn's disease who were refractory or intolerant to anti-TNF therapy, Battat et al observed mean ustekinumab trough concentrations of 4.7 and 3.8 μg/mL in patients with and without endoscopic response, respectively, while on maintenance therapy of ustekinumab 90 mg primarily every four weeks (42 of 56 patients) [12].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with Crohn's disease who were refractory or intolerant to anti-TNF therapy, Battat et al observed mean ustekinumab trough concentrations of 4.7 and 3.8 μg/mL in patients with and without endoscopic response, respectively, while on maintenance therapy of ustekinumab 90 mg primarily every four weeks (42 of 56 patients) [12]. Finally, increased mucosal inflammation has been proposed to decrease ustekinumab trough levels by increased production of IL-12 and IL-23, which then consumes ustekinumab [11]. Numerous studies which exhibit that intensifying ustekinumab decreases loss of response in Crohn's disease patients support this mechanism [13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%